Evaluating Physical Functioning in Survivors of Critical Illness: Development of a New Continuum Measure for Acute Care*. Issue 10 (October 2020) - Parry, Selina M.; Knight, Laura D.; Baldwin, Claire E.; Sani, Diana; Kayambu, Geetha; Da Silva, Vinicius Maldaner; Phongpagdi, Pimsiri; Clarke, Sandy; Puthucheary, Zudin; Morris, Peter; Denehy, Linda; Granger, Catherine L.
Abstract : Objectives: Evaluation of physical functioning is central to patient recovery from critical illness—it may enable the ability to determine recovery trajectories, evaluate rehabilitation efficacy, and predict individuals at highest risk of ongoing disability. The Physical Function in ICU Test-scored is one of four recommended physical functioning tools for use within the ICU; however, its utility outside the ICU is poorly understood. The De Morton Mobility Index is a common geriatric mobility tool, which has had limited evaluation in the ICU population. For the field to be able to track physical functioning recovery, we need a measurement tool that can be used in the ICU and post-ICU setting to accurately measure physical recovery. Therefore, this study sought to: 1) examine the clinimetric properties of two measures (Physical Function in ICU Test-scored and De Morton Mobility Index) and 2) transform these measures into a single measure for use across the acute care continuum. Design: Clinimetric analysis. Setting: Multicenter study across four hospitals in three countries (Australia, Singapore, and Brazil). Patients: One hundred fifty-one ICU patients. Interventions: None. Measurements and Main Results: Physical function tests (Physical Function in ICU Test-scored and De Morton Mobility Index) were assessed at ICU awakening, ICU, and hospital discharge. A significant floor effect was observed for the De Morton Mobility Index at awakening (23%) and minimal ceiling effects across all time points (5–12%). Minimal floor effects were observed for the Physical Function in ICU Test-scored across all time points (1–7%) and a significant ceiling effect for Physical Function in ICU Test-scored at hospital discharge (27%). Both measures had strong concurrent validity, responsiveness, and were predictive of home discharge. A new measure was developed using Rasch analytical principles, which involves 10 items (scored out of 19) with minimal floor/ceiling effects. Conclusions: Limitations exist for Physical Function in ICU Test-scored and De Morton Mobility Index when used in isolation. A new single measure was developed for use across the acute care continuum. Abstract : Supplemental Digital Content is available in the text.